Stabilized biomass ash as a sustainable substitute for commercial P‐fertilizers. (8th March 2018) - Pasquali, Michela; Zanoletti, Alessandra; Benassi, Laura; Federici, Stefania; Depero, Laura E.; Bontempi, Elza
Abstract: The reuse of biomass ash as a fertilizer is generally recognized as good practice with several environmental benefits. However, the possible presence of leachable heavy metals in this ash limits the potential extent of its application and the implementation of an appropriate legal framework. For the first time, a method to stabilize wood ash based on the use of other by‐products (coal fly ash and rice husk ash) is presented. No commercial chemicals are employed in the procedure. The results show that despite the initial presence of leachable heavy metals in the ash, the final obtained material is stable. In addition, the lowering of pH (from 13.5 to approximately 7.5) due to carbonation reactions and the addition of Ca‐rich ash increases the phosphorous availability compared with the starting wood ash and makes the obtained material suitable for use in soil fertilization. The sustainability of the new proposed technology is quantitatively discussed with regard to the differences in embodied energy and CO2 footprint of phosphorous between raw materials and stabilized wood ash. This work shows that the prospects for energy saving and CO2 footprint reduction using stabilized wood ash as a substitute for inorganic commercial P‐fertilizers are significant and offer a new way to reach these objectives. The simplicity of the method and the general availability of the by‐products employed in the stabilization also render the procedure suitable for applications in developing countries.